Keanekaragaman, Persebaran dan Pemanfaatan Jenis-Jenis Anggrek (Orchidaceae) di Resort Citorek, Taman Nasional Gunung Halimun-Salak, Jawa Barat - Asep Sadili (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
Diversity, distribution, and utilization of orchids have been studied on the mountains of Halimun-Salak National Park. Samples were taken from Citorek Resort with focused exploration on Citorek, Lebaktugu, Cinakem, Cibedug, and Ciawitali areas. The total,of 107 species belonging to 46 genera were recorded. As many as 27 species were recorded as javanese endemic species of Indonesian islands. Most species have no economic value and only a few orchids have been cultivated. The Calanthe, Cymbidium, Phaius and Renanthera have been used for cross breeding.